Analysis of Media Relations Activities in The Public Relations Model (Case Study on Public Relations of DPRD Ponorogo Regency) - Rahman, Alwi; Setiawan, Veri (LITERAKOM: Jurnal Literasi dan Komunikasi, 2024)
This study aims to analyze media relations activities carried out by public relations of the Ponorogo Regency DPRD in the public relations model. By using four Grunig public relations models, namely Press Agentry / Publicity, Public Information, Two-Ways Asymmetrical, Two-Ways Symmetrical. This research uses a qualitative approach with a case study method. The results of this study show that the Public Relations of the Ponorogo Regency DPRD uses the press agentry/publicity model to obtain the widest coverage of information and spread a positive image of the institution. The Public Relations of the DPRD Kabupten Ponorogo uses the public information model to disseminate fast, precise, and accurate information. The Public Relations of the Ponorogo Regency DPRD uses a two-ways asymmetrical model more towards a communication approach that focuses on maintaining a positive image. With the two-way symmetrical model, the public relations of the Ponorogo Regency DPRD strives to provide useful information, maintain good communication with the community.